تأثير عقار السبروفلوكساسين على مستوى خميرة الفوسفاتيز القاعية في الفئران السليمة - Alumar, Luma W.K. (The Iraqi Journal of Veterinary Medicine, 1999)
This study was designed to investigate the effects of ciprofloxacin on-serum alkaline phosphates level in normal mice , the dosage used is treatment and double dose (5 10 mg / kg ) orally for 5 days . The result showed that ciprofloxacin caused a marked increase in serum alkaline phosphates with the increase of dose, and this may be releated to the damage of cell in liver , kidney and bone